Боспорські міфи в ілюстраціях аттичних вазописців IV ст. до н. е. - Скржинська, М.В. (Археологія, 1997)
У статті розглядається серія аттичних ваз IV ст., розписаних з урахуванням смаків мешканців Боспора; досліджено вплив вазопису на складання зорових образів героїв популярних міфів; виділяються невідомі за писемними джерелами варіанти поширених на Боспорі міфів про викрадення Європи, про амазонок, арімаспів і пігмеїв. В статье рассматриваются аттические вазы IV в. до н. э., изготовленные для целенаправленного экспорта из Афин на Боспор. На этих вазах иллюстрируются популярные на Боспоре мифы, связанные с представлением о переходе души умершего в потустороннее царство; сражения амазонок с греками, борьба амазонок и аримаспов с грифонами, битва пигмеев с журавлями и похищение Европы Зевсом. Художественное воплощение мифов на рисунках ваз оставалось чисто аттическим, так что боспоряне видели героев своих мифов глазами афинских художников. Многофигурные композиции способствовали более подробному изложению мифов и введению в них второстепенных персонажей. Особая ценность рассмотренных рисунков определяется тем, что они — единственное свидетельство об особых вариантах общегреческих мифов, которые не сохранились в античной литературе. Attic vases of the 4th cent. B. C. made for purposeful export from Athens to Bosporus are described in this paper. Pictures made on these vases illustrate myths popular in Bosporus and associated with imagination of a transfer of the deceased’s soul to the other world; battles of the Amazons and the Greeks, fight of the Amazons and Arymasps against gryphons, struggle between the pygmies and cranes, abduction of Europe by Zeus. Artistic embodiment of the myths on the pictures painted on vases was purely Attic, so the Bosporus people saw heroes of their myths with the eyes of Attic painters. Multifigure compositions contributed to more detailed narration of the myths and, moreover, to introduction of accessory characters. The particular value of these drawings is that they are a unique testimony to peculiar variants of all-Greek myths, which were not preserved in the antique literature.